A cognitive approach to irritable bowel syndrome - Chapman, S; Miss S. C. E. Chapman (2012)
Within this thesis the role of cognitive processes in irritable bowel syndrome (IBS) will be examined. A systematic review and meta-analysis of the rate of psychiatric comorbidity in IBS participants, relative to controls, was performed. Evidence supported heightened rates of psychiatric disorder. A novel hypothesis regarding overlapping cognitive vulnerability to IBS and psychiatric disorders was found to fit well with the pattern of comorbidity. Competing hypotheses and the potential moderators were examined. Overall, no single model of psychiatric morbidity in IBS could fully account for the results of the meta-analysis. The implications of this meta-analysis for a cognitive approach to IBS are discussed. Cognitive processes were directly investigated in two experiments. First, in a modified exogenous cueing task, which assessed attention to pain words, there was faster orienting towards, and engagement with pain words in IBS participants relative to controls. Next, participants completed a primed lexical decision task, which indexed interpretation biases by measuring response times to targets after ambiguous illness primes. Relative to controls, IBS participants’ responses were slower to target words presented after ambiguous illness primes, and demonstrated priming for targets related to the neutral meaning of the illness prime. In the second study, different IBS and healthy control participants completed an internet-based survey of autobiographical memory. Participants described and rated painful and emotional autobiographical events. IBS participants reported pain memories from a more observer perspective relative to controls, suggesting a possible coping strategy for pain content. Finally, three cognitive styles, alexithymia, rumination and self-blame, were evaluated using existing and novel self-report measures. Overall, when compared with healthy participants, IBS participants reported: less difficulty identifying feelings as indexed by the alexithymia measure; increased pain-focused rumination; and a general, negative self-blame. These results may imply a vigilance-avoidance model of cognitive processing in IBS.